Balinese Language Contribution to The Spread of Hindu Educational Values - Sugiharta, I Putu Suweka Oka; Herawan, Kadek Dedy (International Journal of Multidisciplinary Sciences, 2025)
The educational process becomes more effective if it is disseminated in local ways so that it is easier to understand. In a community, the best way to carry out the educational process is to utilize a cultural approach. This also applies to religion-based education. The values of religious education must be disseminated by functioning local cultural elements. The most prominent thing about the use of the Balinese language to socialize Hindu teachings in Bali is its success in building a sense of familiarity. From time to time, the Balinese have accepted Hinduism as an integral part of their lives. This sense of closeness is an important point in the educational process. A sense of closeness will ensure the application of educational values. Various forms of oral and written works that appear later can integrate with the educational values of Hinduism. This study aims to describe the role of the Balinese language in the socialization of Hindu religious and educational values. It is clear that the mission alignment between Balinese and Hinduism is complementary and does not interfere with each other. This research method is qualitative, with a descriptive research concentration.